1992
DOI: 10.1042/bj2860585
|View full text |Cite
|
Sign up to set email alerts
|

Increased intestinal protein synthesis during sepsis and following the administration of tumour necrosis factor α or interleukin-1 α

Abstract: The influence of sepsis on intestinal protein synthesis was studied in rats. Sepsis was induced by caecal ligation and puncture (CLP); control rats were sham-operated. Protein synthesis was measured in vivo in the jejunum and ileum following a flooding dose of [14C]leucine. At 8 h after CLP the protein synthesis rate was increased by approx. 15% in jejunal mucosa, and at 16 h after CLP, the protein synthesis rate was increased by 50-60% in the mucosa and seromuscular layer of both jejunum and ileum. In a secon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
13
0

Year Published

1997
1997
2007
2007

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(18 citation statements)
references
References 34 publications
5
13
0
Order By: Relevance
“…has been shown that an acutely induced systemic inflammation results in increased protein catabolism and altered protein synthesis (24,33), showing the importance of inflammation in protein metabolism. Furthermore, chronic inflammation induced by DSS treatment in rats resulted in a stimulation of protein synthesis in various splanchnic organs, i.e., the spleen and intestine, whereas muscle protein turnover was reduced (24).…”
Section: Discussionmentioning
confidence: 99%
“…has been shown that an acutely induced systemic inflammation results in increased protein catabolism and altered protein synthesis (24,33), showing the importance of inflammation in protein metabolism. Furthermore, chronic inflammation induced by DSS treatment in rats resulted in a stimulation of protein synthesis in various splanchnic organs, i.e., the spleen and intestine, whereas muscle protein turnover was reduced (24).…”
Section: Discussionmentioning
confidence: 99%
“…Animals from each group received a bolus intravenous injection of L-[ l-'3C]valine (150 pmo1/100 g body weight, 30 atom% excess, 0.5 m1/100 g body weight) (~-[l-'~C]valine, 99 atom% from Mass Trace, Woburn, MA, U.S.A.). In each group, one animal was killed by decapitation after anaesthesia with sodium pentobarbital (6 mg/100 g body weight) at 4,8,12,16,20,24,28,36,44 and 52min after the tracer injection. Times from 4 to 24 min were used for the determination of liver and intestine protein synthesis rates, in order to take into account the synthesis of exported proteins.…”
Section: Measurement Of Protein Synthesismentioning
confidence: 99%
“…Previous studies suggest that the enterocyte and intestinal mucosa participate in the inflammatory and metabolic responses to sepsis and endotoxaemia [1][2][3][4]. For example, we recently found evidence that the acute-phase protein complement component C3 is produced in the mucosa of the small intestine after injection of endotoxin in mice [5], and in cultured Caco-2 cells (a human intestinal epithelial cell line) following treatment with interleukin-1β (IL-1β) described in cells subjected to hyperthermia [14].…”
Section: Introductionmentioning
confidence: 99%